Penataan Ruang Kota Kecamatan Bungoro Kabupaten Pangkajene dan Kepulauan Berbasis Kajian Sistem Transportasi - Laode Muh. Asfan Mujahid; Moh. Yoenus Usman; Muhammad Fathien Azmy (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2015)
Arrangement of a region's transportation system is basically often adjusted to the needs and availability of regional space and other supporting facilities in an effort to meet the needs of the community in terms of the environment and aspects of the regional economy. The purpose of this study is to identify the characteristics of the transportation system, identify the influence of PT. Semen Tonasa, and formulate the concept of urban spatial planning in Bungoro District, Pangkep Regency based on the study of regional transportation systems on spatial patterns. The analytical method used is qualitative descriptive analysis, spatial mapping (overlay), and mapping. The results of this study indicate that the characteristics of the transportation system in Bungoro District still do not meet the standards in terms of supply. Furthermore, from the analysis of the transportation system of PT. Semen Tonasa can be concluded that the transportation system of PT. Semen Tonasa influences the spatial pattern of Bungoro District, especially land use changes in several regions. Meanwhile, the concept of urban spatial planning in Bungoro District is based on a study of transportation systems in the form of directions for developing alternative routes for PT. Semen Tonasa so that it does not interfere with community transportation activities in Bungoro District.